2022
DOI: 10.1097/op9.0000000000000043
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and perspectives on the future of oncology pharmacy—collated results of member surveys of the European Society of Oncology Pharmacy

Abstract: Introduction:The European Society of Oncology Pharmacy (ESOP) has nearly 4000 members in 66 countries. Periodically, the needs and interests of the members as well as the predictions of the members for the development of the profession of oncology pharmacy are mapped by the board of the Society. The aim of these inquiries is to help focus the Societies' advocacy works, knowledge exchange, and scientific and educational programs into those areas where the members deem this most needed.Methods: One survey into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
1
0
0
Order By: Relevance
“…4 A previous study on the beliefs and perspectives of ESOP members showed that 95% of members believe that increasing interaction between doctors and pharmacists will be required shortly and overall clinical pharmacy yielded the highest interest rates from a panel of 16 pharmacy topics. 10 The current results reinforce those findings.…”
Section: Discussionsupporting
confidence: 89%
“…4 A previous study on the beliefs and perspectives of ESOP members showed that 95% of members believe that increasing interaction between doctors and pharmacists will be required shortly and overall clinical pharmacy yielded the highest interest rates from a panel of 16 pharmacy topics. 10 The current results reinforce those findings.…”
Section: Discussionsupporting
confidence: 89%